Towards a Theology of Childhood: Children's Agency and the Reign of God: - McEvoy, James Gerard (Theological studies, 2019)
This article contributes to a theology of childhood in the context of recent research in the social sciences on children's lives and the nature of childhood. The clergy sexual abuse crisis heightens the need for such a theology. First, the author offers an account of children's social agency, with particular attention to cognition and sociality, arguing that an interpretative approach affords the best account. Second, the argument takes a christological turn, examining Jesus's welcoming of children and the statement "it is to such as these that the kingdom of God belongs" (Mark 10:14), to consider what can be learnt about Jesus's appreciation of children's agency.